Novel FabI inhibitor disrupts the biofilm formation of MRSA through down-regulating the expression of quorum-sensing regulatory genes. (February 2022) - Zheng, Yan; Lu, Xueer; Liu, Biyong; Li, Bo; Yang, Chengwei; Tang, Wenjian; Zhang, Jing
Abstract: Objectives: The aim of this study was to explore the antibiofilm and antivirulence efficacy of benzylaniline 4k against MRSA. Methods: The clinical MRSA strains were identified and used to evaluate their potential to form biofilm using crystal violet assay. The minimal inhibitory concentration (MIC) was determined using broth microdilution method. The expression of genes was detected using quantitative real-time PCR (qRT-PCR). Rabbit blood hemolytic assay was used to observe the inhibitory ability of alpha-hemolysin (Hla). Results: Compound 4k showed potent antibacterial activity against 16 clinical MRSA with an MIC50 of 1.25 mg/L and MIC90 of 2.25 mg/L. The value of minimum biofilm eradication concentration (MBEC) against MRSA2858 biofilm was of 1.5 mg/L, close to its MIC, superior to those of vancomycin and erythromycin. Compound 4k eradicated the formation of biofilm through inhibiting the gene expression of branched-chain fatty acid synthesis, down-regulating the expression of quorum-sensing (QS) regulatory genes ( norA, agrA, icaA, hla ), decreasing the level of hemolysis in a dose-dependent manner, and inhibiting rabbit blood hemolysis by 86.9% at a concentration of 1.25 mg/L. In a mouse model of abdominal infection, compound 4k was more effective than vancomycin in reducing bacterial load. Conclusions: These results suggested that compound 4k could be developed as promising an anti-MRSA agent through affecting quorum-sensing system. Graphical abstract: Image 1 Highlights: FabI inhibitor 4k showed antibiofilm activity against clinical MRSA. 4k displayed the activity through down-regulating fabI and bkd genes. 4k interrupted the expression of QS regulatory genes norA, agaA, icaA, hla . In vivo 4k was more effective than vancomycin in reducing bacterial load.